Parking for CineCulture's Hispanic Heritage Month film 'La Americana' Sept. 20 - Uribes, Tom::::::::: (2013)
Guests attending Fresno State's CineCulture screening of 'La Americana,' can park for free on campus if they inform parking officers they are attending the screening.